Diurnal variation in summer precipitation over the central Tibetan Plateau - Nakamura, Kenji; Singh, Prasamsa (My University, 2009)
The diurnal cycle of rainfall over the central Tibetan Plateau was investigated by examining data acquired by the Tropical Rainfall Measuring Mission Precipitation Radar during the summer monsoon season (June–August) from 1998–2007. High-spatial-resolution data ( 5 km 5 km) were used to identify the role of complex topographic features of the plateau. Diurnal variations in rain rate, frequency of rain, conditional rain rate, and storm-height were analyzed on a monthly basis to determine the characteristics of precipitation. The results are interpreted as precipitation characteristics in a semiarid region with weak prevailing winds. Distinct diurnal variation was seen over hilly regions, valleys, and lakes. Precipitation activity over the hilly region is generally strongest during the late afternoon. But in contrast, valleys and lakes show dominant late-evening peaks, and a secondary morning rainfall peak is distinctly evident over large lakes. However, the time of peak rain rate is delayed with increasing lake size. The shift in rain peak location toward lakes and valleys also appeared clearly. Copyright American Geophysical Union.
Keywords: diurnal variation; TRMM/precipitation radar; Tibetan Plateau